2015
DOI: 10.1093/scan/nsv046
|View full text |Cite
|
Sign up to set email alerts
|

Sending mixed signals: worry is associated with enhanced initial error processing but reduced call for subsequent cognitive control

Abstract: Worry is reliably associated with overactive action-monitoring processes as measured by the error-related negativity (ERN). However, worry is not associated with error-related behavioral adjustments which are typically used to infer increased cognitive control following errors. We hypothesized that this disconnect between overactive action monitoring and unimproved post-error adjustments in worriers is the result of reduced functional integration between medial and lateral prefrontal regions during generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 67 publications
(91 reference statements)
0
29
0
Order By: Relevance
“…We recently investigated potential mechanisms to explain the disconnect between a larger ERN and the failure of anxious adults to adaptively change their behavioral performance (Moran et al 2015). Findings suggested that this disconnect was a result of decreased theta band synchrony, indicative of reduced connectivity between medial frontal and lateral pre-frontal regions associated with the generation of the ERN.…”
Section: Discussionmentioning
confidence: 99%
“…We recently investigated potential mechanisms to explain the disconnect between a larger ERN and the failure of anxious adults to adaptively change their behavioral performance (Moran et al 2015). Findings suggested that this disconnect was a result of decreased theta band synchrony, indicative of reduced connectivity between medial frontal and lateral pre-frontal regions associated with the generation of the ERN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study found that while worry was associated with increased neural reactivity to conflict, this anxiety was not associated with enhanced connectivity (i.e., theta phase synchrony; ) between medial and lateral electrode sites (Moran, Bernat, Aviyente, Schroder, & Moser, 2015). This latter finding suggests that despite reacting more strongly to conflict, anxious individuals are less able to use this signal to improve control.…”
Section: Anxiety Acceptance and Improving Cognitive Controlmentioning
confidence: 93%
“…Somewhat notably, the type of task itself does not seem to play a role in whether a study will find a relative increase or a decrease in accuracy after errors. For example, while several studies using the flanker task have found increases in accuracy following errors compared to correct trials (Grutzmann, Endrass, Klawohn, & Kathmann, ; Marco‐Pallares, Camara, Munte, & Rodriguez‐Fornells, ; Pontifex et al, ; Seifert, von Cramon, Imperati, Tittgemeyer, & Ullsperger, ; Strozyk & Jentzsch, ), other studies using the same paradigm have shown either the opposite pattern (Arnstein, Lakey, Compton, & Kleinow, ; Fiehler, Ullsperger, & von Cramon, ; Franken, van Strien, Franzek, & van de Wetering, ) or no difference between the conditions (Moran, Bernat, Aviyente, Schroder, & Moser, ; van den Brink et al, ). The same picture is true for other tasks, with some studies showing post‐error increases in accuracy (Danielmeier et al, ; Dutilh et al, ; Forster & Cho, ; Klein et al, ), some showing decreases (Bombeke, Schouppe, Duthoo, & Notebaert, ; Carp & Compton, ; Houtman & Notebaert, ; Jentzsch & Dudschig, ; Jonker, Seli, Cheyne, & Smilek, ; Notebaert et al, ; Notebaert & Verguts, ; Van der Borght, Braem, Stevens, & Notebaert, ), and some showing no change (e.g., Hajcak et al, ).…”
Section: Section Ii: Behavioral Studies Of Post‐error Accuracy Are Inmentioning
confidence: 99%